Development and validation of an LC–MS/MS/MS method for the quantification of fluoroquinolones in several matrices from treated turkeys. (February 2015) - Lucatello, Lorena; Cagnardi, Petra; Capolongo, Francesca; Ferraresi, Caterina; Bernardi, Filippo; Montesissa, Clara
Abstract: The study presents a sensitive and reliable confirmatory method for the extraction, identification, quantification of five fluoroquinolones (FQ) namely enrofloxacin, ciprofloxacin, difloxacin, sarafloxacin and flumequine, in plasma, liver, kidney, muscle, skin + fat, lung and intestinal content from turkeys. For the extraction and matrix clean-up of FQ residues from all biological matrices, the Quick Easy Cheap Effective Rugged Safe (QuEChERS) methodology was adopted; only for plasma samples acetonitrile was used. The analyses were performed by liquid chromatography with mass spectrometry detection (LC–MS). LC separation was performed on a C18 Kinetex column (100 × 2.1 mm, 2.6 μm, Phenomenex, CA, USA) with gradient elution using ammonium acetate solution (10 mM, pH 2.5) and methanol containing 0.1% formic acid. Mass spectrometric identification was done using an LTQ XL ion trap (Thermo Fisher Scientific, CA, USA), with a heated electrospray ionization probe, in positive ion mode. The method was validated according to the European Legislation (decision 2002/657/EC) and EMA guideline (EMA/CVMP/VICH/463202/2009); selectivity, linearity response, trueness (in terms of recovery), precision (within-day repeatability and within-laboratory reproducibility), limit of detection, limit of quantification, decision limits, detection capability, absolute recovery and robustness were evaluated using turkey blank matrices. All data were within the required limits established for confirmatory methods except for flumequine which presented a recovery value slightly higher than 110% in muscle and intestinal content. For all FQs, all the extraction rates were greater than 70% and limits of quantification ranged from 1.2 μg kg −1 to 118.8 μg kg −1 . This fast and robust method was suitable for the identification and quantification of FQ residues in tissues, plasma and intestinal content as confirmed by data obtained from incurred samples of turkeys treated at farm for therapeutic purposes. Highlights: An LC–MS method was developed for five fluoroquinolones quantification. The method was validated in seven matrices (tissues and fluids) from turkeys. The fluoroquinolones were detectable in a wide range of concentrations. The method was successfully applied to plasma samples for pharmacokinetic study. Residue distribution and depletion were evaluated for two fluoroquinolones.